Comparison of green design strategies in five traditional Malay houses - Nor Afifah Husen; Mohd Farid Mohamed (Penerbit Universiti Kebangsaan Malaysia, 2021)
The traditional Malay house architecture is undoubtedly one of the ideal green ideal design concepts that can be applied in Malaysian housing development for sustainability. Not only does it have unique features that symbolize national identity, but it is also an important example with various design strategies for habitable space based on local climate and sociocultural aspects. Nowadays, Malaysia’s construction sector has changed due to modernization and being replaced and disintegrated by modern influences. Thus, it erodes the values of the existing green design approaches commonly found in the design of traditional Malay house architecture, that respond well to the local sociocultural and climate conditions. The objective of this study is to identify the green approaches in traditional Malay houses in Malaysia. This study used a qualitative approach, which is a combination of literature studies and site observations. For the site observations approach, it limited to traditional Malay houses from five out of eleven states in Peninsular Malaysia. The investigated traditional Malay houses are from Negeri Sembilan, Pahang, Perak, Terengganu, and Kelantan. The findings of the study show that the architecture of these traditional Malay houses have many green design strategies which prove the sustainability aspect exist in all investigated traditional Malay houses. Thus, this study lists 22 of typically found green design strategies in traditional Malay houses and it can be used as reference or guideline for designing homes in Malaysia.